Low Intensity Pulsed Ultrasound Accelerates Delayed Healing Process by Reducing the Time Required for the Completion of Endochondral Ossification in the Aged Mouse Femur Fracture Model - MIKUNI-TAKAGAKI, Yuko; KATANO, Motoaki; ITOMAN, Moritoshi; TAKASO, Masashi; URABE, Ken; NARUSE, Kouji; UCHIDA, Kentaroo (EXPERIMENTAL ANIMALS, 2011)
The aim of this study is to clarify the effect of low intensity pulsed ultrasound (LIPUS) on shortening of the fracture healing period and endochondral ossification during the fracture healing process. We first established a model of aging-related delayed union fractures consisting of aged mouse (C57BL/6J; 40 weeks old) with closed femur fractures. We compared the healing process of 40-week-old mice to the healing process of 8-week-old (young) mice using radiological and histological analysis. In aged mice, some cartilage formation was observed 10 days after the fracture; however, endochondral ossification and hard callus bridging were observed 21 and 28 days after the fracture, respectively, whereas cartilage remained in the callus on day 28, suggesting delayed endochondral ossification following bone remodeling. Meanwhile, in aged mice with LIPUS treatment, cartilage formation was similar to that in aged mice without LIPUS; however, hard callus bridging and bone remodeling were observed 21 and 28 days after fracture, respectively, suggesting that LIPUS shortened the healing period due to promotion of endochondral ossification. Immunohistochemical analysis showed marked expression of vascular endotherial growth factor and neovascularization in the fibrous tissue comprising the periosteum that surrounded the whole callus. A cell migration test involving primary cultured human endothelial cells also showed promotion of cell migration by LIPUS. These results suggested that endothelial cell migration and neovascularization, which were observed around fracture sites, played a part in the mechanism of promotion of endochondral ossification by LIPUS.